DESCRIPTION OF MENSTRUAL CYCLE DISORDERS IN 3 MONTHS INJECTABLE CONTRACEPTIVE USERS - Mardhika, Amellia; Safitri, Yolanda Dwi; Fadliyah, Lailatul; Medawati, Riris (Journal of Vocational Nursing, 2021)
Introduction: Injectable contraception (3-month) is a hormonal contraceptive that is widely used by women of childbearing age because it is very effective in preventing pregnancy, and includes the Intermediate- term Method. The use of 3-month injectable contraceptives also has drawbacks or side effects, one of which is menstrual cycle disorders. The purpose of this study was to determine the description of menstrual cycle disorders in users of 3-month injectable contraceptives. Methods: This study used a descriptive design. The population in this study was women of childbearing age who used injection contraception for 3-months at the sub-health center of Tanjung Village. The total population in this study was 48 samples. The sampling technique was carried out by the total sampling technique. The statistical analysis used in this study was descriptive analysis (number and prosentase). Results: The results of the study showed that using 3-month injectable contraceptives were found that 29 respondents (60.4%) experienced amenorrhea, 15 respondents (31.3%) spotting, and 4 respondents (8.3%) did not experience menstrual cycle disorders. Conclusion: Most users of 3-month injectable contraceptives experience amenorrhea.